The relationship of entrepreneurship education, financial literacy, family environment, attitude to finance, and student entrepreneurial interest - Simanungkalit, Ate Gueen; Kainde, Sandra J. R.; Tumbel, Jerry Noldin (Universitas Jambi, Indonesia, 2026)
This study examined the influence of entrepreneurship education, financial literacy, family environment, and attitudes towards finance on entrepreneurial interest among students of the Faculty of Economics and Business at Universitas Klabat. It involved 210 students (144 from the Management Study Program and 66 from the Accounting Study Program) who completed an Entrepreneurship course. A 5-point Likert-scale questionnaire was used to measure four independent variables and one dependent variable, yielding a Cronbach's alpha of 0.868. Descriptive statistics indicated high scores on the variables studied, and no significant differences in entrepreneurial interest between study programs and genders. Entrepreneurial interest is positively and significantly related to entrepreneurship education, financial literacy, family environment, and attitudes towards finance. Campus entrepreneurial knowledge and family support contribute to increased interest in entrepreneurship. Regression analysis identified entrepreneurial education, family environment, and attitudes towards finance as significant predictors, though their contributions were moderate, suggesting a need for further research on other factors.